Bridging the Divide between Being and Knowing: In Quest of Care-Ethical Agency - Beck, Kumari; Cohen, Avraham; Falkenberg, Thomas (Paideusis, 2007)
Taking up the theme of this year’s Congress – Bridging communities: Making public knowledge, making knowledge public – our panel’s three essays each examines from three different locations how knowledge and knowledge-making function in the contemporary market/knowledge economy: international education, autobiographical inquiry, and teacher education. The educational vision and commitment that these three distinct pieces share is ethics of care. Problematizing commodification of knowledge and its notion of having knowledge, we make the case for the centrality of being in human and societal living. We then make suggestions for how the being-dimension can be conceptualized and lived. In particular, we argue that caring, being present, self-knowing and human agency are central.